ANALISIS KINERJA KEUANGAN BERDASARKAN RASIO LIKUIDITAS, SOLVABILITAS, DAN PERTUMBUHAN LABA PT WIJAYA KARYA (PERSERO) TBK - Aini, Suci Aulia Nurul; Puji Muniarty (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the financial performance of PT Wijaya Karya (Persero) Tbk based on liquidity, solvency, and profit growth ratios. Financial performance anlysis is essential for evaluating a company’s abilitiy to manage its financial resources effectively. The method used in this study is a descriptive quantitative approach using secondary data abtoined from the company’s financial statement. The analysis focuses on key financial ratios, including Current Ratio (CR), Dept to Asset Ratio (DAR), as well as profit growth to measure the company’s ability to increase earnings. The result show that the company’s liquidity is relatively stable, although fluctuations occur in certain periods. The solvency ratio indicates in considerable reliance on debt, which may increase financial risk but remains mangeable. Meanwhile, profit growth tends to fluctuate, imfluenced by operational performance and external economic conditions. Overall, the financial performance of PT Wijaya Karya (Persero) Tbk can be considered fairly good, although improvements are still needs in managing debt and enhancing profitabilility.